2020
DOI: 10.1177/2325967120911162
|View full text |Cite
|
Sign up to set email alerts
|

Bone Bruise Distribution Patterns After Acute Anterior Cruciate Ligament Ruptures: Implications for the Injury Mechanism

Abstract: Background: Bone bruises observed on magnetic resonance imaging (MRI) after an anterior cruciate ligament (ACL) injury could provide significant information about ACL injury mechanisms. Purpose/Hypothesis: The purpose of this study was to investigate common bone bruise patterns after an ACL injury. It was hypothesized that the most common bone bruise distribution pattern would be only the lateral side of both the femur and tibia. Study Design: Cross-sectional study; Level of evidence, 3. Methods: Knee MRI scan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

10
61
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 27 publications
(72 citation statements)
references
References 38 publications
10
61
1
Order By: Relevance
“…We found that kissing contusions occurred more commonly in the posterior aspect of the tibial plateau and the femoral condyle's central aspect. Consistent with previous studies (2,17), lateral femoral condyle's most common pattern in patients with LKCs was the centrallateral. Previous studies have reported that tibial bone contusions occur in the posterior section.…”
Section: Discussionsupporting
confidence: 90%
See 4 more Smart Citations
“…We found that kissing contusions occurred more commonly in the posterior aspect of the tibial plateau and the femoral condyle's central aspect. Consistent with previous studies (2,17), lateral femoral condyle's most common pattern in patients with LKCs was the centrallateral. Previous studies have reported that tibial bone contusions occur in the posterior section.…”
Section: Discussionsupporting
confidence: 90%
“…The severity and the location patterns of tibiofemoral bone contusions observed on the magnetic resonance imaging scans may result from joint impact at the time of anterior cruciate ligament injury and could provide important information about anterior cruciate ligament injury mechanisms (6,17,20,21). Previous studies have investigated the mechanisms of anterior cruciate ligament injuries using patterns of kissing bone contusions.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations